Implementasi Kompetensi Kewirausahaan Kepala Sekolah dalam Upaya Meningkatkan Kesejahteraan Guru di MI Ma’arif NU Hidayatul Mubtadiin Padangasri Jatirejo Mojokerto - Siti Khoiriyah; Fadly Usman; Ashari Ashari (Universitas Palan, 2023)
This study aims to determine the implementation of entrepreneurial competence of school principals in an effort to improve teacher welfare at MI Ma'arif Nu Hidayatul Mubtadiin Padangasri Jatirejo Mojokerto with a research focus: How is the implementation of entrepreneurial competence of school principals in an effort to improve teacher welfare, what are the supporting and inhibiting factors of head entrepreneurial competence schools in improving the welfare of teachers MI Ma'arif NU Hidayatul Mubtadiin Padangasri Jatirejo Mojokerto The method used is a qualitative approach with a case study approach. Data collection techniques are used by observation, interviews and documentation studies. Data analysis techniques are made by data reduction, data display and conclusion (verification) and data validity. The results of this study indicate that: (1) indicate that the implementation of entrepreneurial competence of school principals is reflected in various innovative programs, such as the English-based Billingual Program, Student Shuttle Car, and Morning Prayer (TPQ). Commitment to work hard, have motivation, the principal also pays attention to the welfare of teachers with various forms of support, such as payment of salaries according to certification standard salary, THR, health benefits, allocation of BOS funds, and Family Gathering events. (2) Supporting factors include the experience of school principals in entrepreneurship, innovative programs such as the Billingual Program, Morning Prayer (TPQ) and student pick-ups, as well as transparency with all stakeholders. Inhibiting factors include financial constraints and parental constraints. Limited funds affect the implementation of innovative programs. whereas parental constraints such as limited time and understanding of the program may affect their participation